Measuring skill gaps in firms: the PIAAC Employer Module - Marcolin, Luca (OECD Social, Employment and Migration Working Papers, 2023)
This paper introduces the Employer Module of the OECD Survey of Adult Skills (PIAAC), a new OECD survey designed to measure the imbalance between the supply of and demand for the skills needed in the workplace (skill gaps), and how this relates to companies' business strategy and hiring, training and human resource practices. The document first describes the added value of collecting such data, and the different streams of economic research it can contribute to. It then shows how the Module can complement worker-level information on skill imbalances collected in the OECD Survey of Adult Skills. Lastly, it presents the key technical features of the survey, including the questionnaire's conceptual development, the units of observation and coverage, the mode of administration, and the requirements for data cleaning and validation